Thoracic gout tophus with abdominal wall protrusion: A case report. Issue 10 (March 2020) - Kao, Yanbing; Wang, Zhenyu; Leng, Jiali; Qu, Zhigang; Zhuang, Xinming; Ma, Hongyun; Song, Qingxu; Liu, Zijing; Sun, Shuo; Liu, Yi
Abstract: Rationale: A patient presented the abdominal wall protrusion due to tophaceous gout of the spine. Similar cases were not reported in the literature. This study aimed to report a case of tophaceous gout of the spine with abdominal wall protrusion. Patient concerns: A 38-year-old male patient had a 10-year history of gout and hyperuricemia. He complained of back pain and abdominal wall protrusion. Diagnoses: The patient was diagnosed with tophaceous gout of the spine with abdominal wall weakness caused by T11 nerve root compression. Interventions: A semi-lamina decompression was performed at T11-T12. The pathological examination of the specimen demonstrated tophaceous gout of the spine. Outcomes: After the surgery, the patient's back pain was completely relieved and the abdominal wall weakness significant improved. Lessons: This case highlighted that axial gout could mimic thoracic disk herniation clinically. The abdominal wall weakness might also be due to single T11 nerve compression by the tophaceous gout of the spine. In patients with a history of gout, axial gout should be considered as one of the differential diagnoses.